Analisis Ketersediaan Air Pada Sub Kesatuan Hidrologi Gambut Tanjung Leban Provinsi Riau - Yogi Guntara; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Availibility of water at each location are different. This is due to the climate divergence at those locations. The limitation of water availibility and the increasing of its demand have caused several problems, one of them is the deficit of water. Water deficiency is a huge matter on several locations especially provinces with peatlands. In order to analyze water availibility, it can be done by using Mock Method. Mock (1975) has introduced a formulation to calculate stream flow by using rainfall data, evapotranspiration, and hydrology characteristic of flow area to estimate the magnitude of flow in case those data is not affordable. The analysis results have shown that the optimated flow rate by using Mock model factor of 0,910 on August 2017 with 20% of dependable discharge was 1,036 m3/s and the measured discharge was 0,910 m3/s. However, the availibility of water does not have much direct influence towards the number of hotspots. Commonly, the hotspots occurred due to external factor, i.e. human activity.Keywords: Water availibility, Mock method, Hotspots